A Closer Look Into the Characteristics of Fraudulent Card Transactions - Can, Baris; Yavuz, Ali Gokhan; Karsligil, Elif M.; Guvensan, M. Amac (IEEE-INST ELECTRICAL ELECTRONICS ENGINEERS INC, 2020)
Widespread use of Internet also had the substantial impact on the increase of the online card transactions especially with the beginning of the last decade. Along with the increase of online transactions, the worldwide banking sector was forced to deal with or to encounter an unforeseen number of fraudulent activities, yet. Hence, rule-based systems were designed to mark the high-risk transactions and let the experts to confirm the fraudulent nature of such transactions. As a countermeasure, static nature of rule-based systems were exploited by the latest attacks to go undetected. Thus, researchers aimed at designing adaptive fraud detection systems utilizing mainly machine learning techniques with the very recent application of deep learning. However, they were focused on detecting fraudulent activities but, to the best of our knowledge, none of them delved into the better understanding the characteristics of fraudulent card transactions in order to produce more resilient models. Therefore, in this study, we built the biggest data set ever used in a research, consisting of 4B non-fraud and 245K fraud transactions contributed to by the 35 banks in Turkey. Consequently, we introduce and examine the performance of profile-based fraud detection models, namely card-type based model, transaction characteristics based model, and amount-based model. Also, we made temporal and spatial analysis on our data set to show the robustness of the proposed models against aging and zero-day attacks.
Keywords: Credit cards; Machine learning; Banking; Data models; Training; Forestry; Insurance; Fraud detection; profiling; amount range; card-type; transaction characteristics; zero-day attack; amount-based success rate; Computer Science; Engineering; Telecommunications